Pelaksanaan Pemberian Bantuan Hukum Secara Cuma-Cuma Bagi Terdakwa Yang Tidak Mampu - Rahmat, Rahmat (Jurnal Ilmiah Multidisiplin Amsir, 2022)
The aim of this research is to determine the optimization efforts carried out by the Legal Aid Office (Posbakum) at the Mamuju District Court in providing pro bono legal assistance to defendants, as well as to identify the challenges faced by legal advisors in providing pro bono legal assistance to defendants. This study falls under the category of empirical legal research, utilizing a socio-legal research approach, often referred to as "law in action". The legal aid standards encompass litigation legal aid standards, non-litigation legal aid standards, legal aid implementation standards, legal aid provision standards, and budget management reporting standards. Litigation legal aid standards cover cases involving criminal, civil, and administrative law. The provision of litigation legal aid is carried out by lawyers who hold the status of legal aid providers and/or lawyers recruited by legal aid providers.